OUTSOURCING OF HOTELS BUSINESS ENTERPRISES - Mendela, I.Ya. (The actual problems of regional economy development, 2019)
The article analyzes the features of outsourcing in the hospitality industry. Outsourcing implies the existence of business processes that are passed on the basis of the contract of a long period of another organization that simplifies any field of activity which is not basic for a hotel. But, of course, the transfer of certain functions to outsourcing involves some risks for a hotel company. Most often, outsourcing in the hotel are transferred cleaning services. However, there is accounting, catering staff, training new employees, trucking services and etc. Competition in the open market, where the determining role is played not only price and quality of hotel services, but also opportunities to better meet the needs of guests, which reduces the time to market of new value added services, intellectual property ownership and other benefits of the hotel, forcing managers to use new management concepts that cover such concepts as infra- and intramanagement. Today, the management of domestic enterprises of the hotel industry is characterized by unstable trends due to the seasonal fluctuations of demand and inability to create stocks of a specific product – hotel service, so the need for effective management of the hotel. In the process of hotel management when using intra- or inframanagement outsourcing can be divided into two kinds – intellectual (it outsourcing, knowledge management, management staff, legal support) and production (transfer partner of full production cycle of a certain product or its part). Outsourcing in the sphere of services is connected with increase of requirements to the level of competence of managers and widespread use of modern information technology. Outsourcing simplifies the operation of the hotel. The success of the hotel management lies in constant improvement, flexibility and adaptability, initiative and entrepreneurial competence.